Comparison of caribou physical characteristics from Yukon and neighboring caribou herds - Gauthier, David A.; Farnell, Richard F. (Rangifer, 1986)
Data on seven external body measurements of caribou from six woodland and two barren-ground caribou herds from Yukon, Alaska, Alberta and British Columbia were compared. Comparisons between females in the fall and winter and mature males in the fall revealed that (1) barren-ground Porcupine caribou were consistently smaller than caribou from other herds, (2) British Columbia and Alberta caribou tended to be larger than Yukon caribou, or the Alaskan caribou studied, (3) central Yukon caribou were intermediate in body size, (4) no difference was found between Yukon «mountain» and «woodland» type caribou in body size, and (5) the barren-ground Fortymile caribou were more similar in physical characteristics to Yukon woodland or mountain caribou than to those of the barren-ground Porcupine herd. These data support Banfield's (1961) view of a gradient of decreasing physical size from the northern British Columbia — Alberta herds through the Yukon mountain or woodland herds to the northern barren-ground herds.